Opportunities and limitations of using the linguistic category model as a measure of teachers' implicit stereotypes in Germany. (April 2022) - Bonefeld, Meike; Beißert, Hanna
Abstract: The current work focused on how ethnic stereotypes manifest themselves in language. The aim of our research was to investigate whether the Linguistic Category Model (LCM) is applicable to German teachers' language. More precisely, we investigated whether the categories proposed by Semin and Fiedler (1988) and mostly tested in the English-speaking world are applicable to German teachers' language and whether the pattern of Linguistic Intergroup Bias is evident in teachers' language. The analyses of two samples including in- and pre-service teachers (Study 1: N  = 124, 76.6% female; Study 2: N  = 104, 67.6% female) revealed difficulties in applying the LCM to German teachers' language. Further, neither of the two conducted studies found patterns of Linguistic Intergroup Bias in teachers' language. We attribute this to a mismatch between the LCM and the German language and discuss the difficulties and limitations of applying the category system to other languages. Highlights: Investigation of the applicability of the Linguistic Category Model (LCM) (Semin & Fiedler, 1988) to German language. No Language intergroup bias is found in German in- and pre-service teachers language. There is a mismatch of the LCM to German language.